Two new species of Coeliccia Kirby from Yunnan, China (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A.; Zhang, Hao-Miao (Zootaxa, 2020)
Two new species of Coeliccia Kirby are described from Yunnan, China: Coeliccia tongbiguan sp. nov. and Coeliccia yunnanensis sp. nov. (holotype ♂ for both from Tongbiguan National Nature Reserve, Yingjiang County, Yunnan). Coeliccia tongbiguan is allied to Coeliccia hoanglienensis Do, known only from Vietnam. Coeliccia yunnanensis appears to be closely allied to the Coeliccia hayashii–group, also from Vietnam. The fifteen named species of Coeliccia now known to occur in China are listed, twelve of them occur in Yunnan, the presence of Coeliccia didyma (Selys) in the country is confirmed.